The role of dietary factors on blood lead concentration in children and adolescents - Results from the nationally representative German Environmental Survey 2014–2017 (GerES V). (15th April 2022) - Hahn, Domenica; Vogel, Nina; Höra, Christian; Kämpfe, Alexander; Schmied-Tobies, Maria; Göen, Thomas; Greiner, Annette; Aigner, Annette; Kolossa-Gehring, Marike
Abstract: In industrialized nations, human lead exposure has decreased significantly in recent decades. Nevertheless, due to its toxic effects, this heavy metal remains a public health concern with children and adolescents being particularly at risk. In Europe nowadays, oral intake via food and drinking water is the predominant exposure pathway for lead. The objective of the present study was to investigate the association between dietary factors and blood lead (PbB) level of 3- to 17-year-old children and adolescents living in Germany, using data from the fifth German Environmental Health Survey (GerES V) and the Child and Adolescent Health Survey (KiGGS Wave 2). GerES V and KiGGS Wave 2 are two national population-representative studies conducted between 2014 and 2017, including measurement of lead concentrations in blood from 720 children and adolescents aged 3–17 years (mean age = 10.21, SD age = 4.36). Using multiple linear regression, sociodemographic and environmental characteristics as well as dietary factors could be identified as significant exposure determinants of PbB concentrations. Lead intake via domestic tap water was the strongest predictor of elevated PbB levels with 27.6% (p-value< .001) higher concentrations of highest compared to none lead intake via tap water. Other foods which were found to be relevant to PbB levels were meat, fruit, and fruit juice. While meat or fruit consumption were each associated with about 13% (p-value < .05) lower PbB levels, fruit juice drinking was associated with up to 12.2% (p-value = .04) higher PbB levels. In conclusion, results indicate the importance of dietary habits for lead exposure in children and adolescents. To protect vulnerable groups, it is recommended that future research and lead-reducing measures pay more attention to dietary links. Graphical abstract: Image 1 Highlights: Blood lead (PbB) levels above the limit of quantification in all participants. PbB was influenced by sociodemographic, environmental, and dietary factors. Lead intake via domestic tap water was the strongest predictor of elevated PbB. Consumption of meat and fruit (except fruit juice) were associated with lower PbB. Opposed determinants indicate complex interaction of lead intake and kinetics.